Perancangan Board Game Knowledge Dash Sebagai Media Pendukung Program Literasi dan Numerasi Sekolah Dasar - Chris Chalik; Isna Cahyani (LPPM STIKI Malang, 2024)
Numeracy literacy is a skill related to basic mathematics to solve practical problems in various contexts of daily life. Numeracy literacy skills for primary school students can make a real contribution to social, economic and welfare growth for individuals or communities. The results of the PISA (Progamme for International Student Assessment) Assessment that Indonesia participated in showed that the numeracy and science literacy scores of Indonesian students had not reached the average score set by PISA. students' numeracy and science literacy skills are still below the minimum competencies set. This is caused by several factors, including the lack of interest of students to participate in literacy activities. Therefore, this design aims to produce learning media that can increase interest and support students' literacy and numeracy programs in the form of educational games in Board game format. The results of this design can be a solution to increase student motivation in implementing literacy and numeracy activities, and also support literacy and numeracy programs. This research uses a qualitative method with an R&D design method. Through this design, it is expected to provide an effective solution in increasing elementary school students' interest in literacy and numeracy.